Evaluation Of ‘Dashanga Agada’ (Herbo-Mineral Compound) In The Management Of Scorpion Sting Envenomation - Binorkar, Sandeep V.; Sreekrishnan, C. M.; V, Asha K. (Asian Journal of Pharmaceutical Research and Development, 2013)
Despite scorpions being locally abundant in many parts of the world, scorpion sting is a poorly defined clinical condition. It is an overwhelming & an endemic public health problem in some part of the India. Scorpion sting can result in a wide range of clinical effects such as neurotoxicity, cardiotoxicity and respiratory dysfunction including pulmonary edema. Ayurveda recommend several medicinal preparations for the management of scorpion sting but so far very little statistical data is available regarding the efficacy of these medicines. This Paper focuses on the efficacy of one of such preparations, Dashanga Agada which was a part of research as internal medication. Clinical study was conducted in 2005 at Pappinissery Visha Chikitsa Kendra, Kannur. Total 10 subjects suffering from Scorpion sting satisfying inclusion criteria were selected and after obtaining informed written consent, treated with Dashanga Agada for four days. Thorough clinical assessment was done before and after the treatment. The result was analyzed statistically with paired t-test which was found highly significant in reducing the cardinal symptom, pain, erythema & inflammation in scorpion sting (P<0.001). Drug also proved effective in reducing other associated symptoms like burning sensation & itching sensations in Scorpion sting. ><0.001). Drug also proved effective in reducing other associated symptoms like burning sensation & itching sensations in Scorpion sting.